2006
DOI: 10.1002/eji.200535142
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal B‐2 cells comprise a distinct B‐2 cell population with B‐1b‐like characteristics

Abstract: B‐1 and B‐2 cells are lymphocyte populations that differ in development, surface marker expression, tissue localization, and function. Though mainly found in the spleen, lymph nodes, and circulation of mice, small numbers of B‐2 cells are found in the peritoneal cavity, a site predominantly populated by B‐1 cells. Here, we characterized peritoneal B‐2 cells, and determined their relationship to B‐1 cells. We found that peritoneal B‐2 cells appear to be intermediate between splenic B‐2 and peritoneal B‐1 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 40 publications
3
45
0
1
Order By: Relevance
“…B2p cells fell in between in both measurements (Fig. 1A, B), in keeping with previous work [17]. The same hierarchy of APC function was also observed in mixed lymphocyte reactions (MLR) ( [15] and Zhong, unpublished data).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…B2p cells fell in between in both measurements (Fig. 1A, B), in keeping with previous work [17]. The same hierarchy of APC function was also observed in mixed lymphocyte reactions (MLR) ( [15] and Zhong, unpublished data).…”
Section: Resultssupporting
confidence: 90%
“…Recently, we also reported that B2 cells in the peritoneal cavity (B2p) differ from both B1p and B2s cells and express many characteristics at levels intermediate between the two [17]. We first investigated the relative capacity of these B cell subsets in presenting OVA peptide to OVA-responsive transgenic T cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the ELISPOT data, we estimate that this Ig-secreting subcompartment constitutes ϳ1% of the B-1 and MZ populations. It has recently been shown that peritoneal B-2 cells express some B-1b cell-like features (17), thus suggesting that the B cell functional attributes could also be shaped by the anatomical microenvironment. Our present data show that, despite these similarities, peritoneal B-2 cells behave like splenic FO B cells in response to TLR agonists.…”
Section: Discussionmentioning
confidence: 99%
“…However, peritoneal B2 cells appear to constitute a unique B cell subset, which exhibits characteristics that are intermediate between peritoneal B1 cells and splenic B2 cells. Peritoneal B2 cells additionally acquire certain characteristics of B1 B cells upon residing in the peritoneal cavity [25]. CD11b, moreover, has been suggested to distinguish different developmental stages of peritoneal B cells [26] and its expression depends upon the location within the peritoneal cavity [27].…”
Section: Discussionmentioning
confidence: 99%